Characteristics and storage stability of vegetable incorporated kutsinta - Chiongson , Jasmin Tan (2001.)
Effects of vegetable incorcporation on the sensory attributes anf the physico-chemical properties of traditional kutsinta were investigated.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Vegetable